Morton's Neuroma Excision: What Are We Really Doing? Which Retractor Is Superior?. Issue 3 (June 2019) - Pinter, Zachariah; Odom, Christopher; McGee, Andrew; Paul, Kyle; Huntley, Samuel; Johnson, John L.; Shah, Ashish
Background: When using a dorsal approach for Morton's neuroma excision, the most common complication is recurrent Morton's neuroma. The present cadaveric study demonstrates how far proximally the nerve is resected during a dorsal approach and examines both the laminar spreader and Gelpiretractor to determine which instrument facilitates maximal proximal resection of the nerve. Methods: This study involved 12 fresh-frozen cadaver specimens, each of which underwent a dorsal approach to the interdigital nerve with proximal resection. Either a laminar spreader or a Gelpi retractor was used to improve visualization of the intermetatarsal space. The interdigital nerve was then resected, and the lengths of the cut nerves were compared based on the retractor employed. Results: The mean length of proximal resection in the second intermetatarsal space was 2.42 cm when using the laminar spreader and 1.93 cm when using the Gelpi retractor (P = .252). In the third intermetatarsal space, the mean length of proximal resection was 2.14 cm when using the Laminar spreader and 1.48 cm when using the Gelpi retractor (P = .166). Conclusion: This study demonstrates how far proximal the interdigital nerve is resected during a dorsal approach to Morton's neuroma and shows no statistically significant difference between the Laminar spreader and the Gelpi retractor. Levels of Evidence: Level V: Cadaver study